Large-scale Production of Paper-based Li-ion Cells - Zolin, Lorenzo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes in detail the use of natural cellulose fibers for the production of innovative, low-cost, and easily recyclable lithium-ion (Li-ion) cells by means of fast and reliable papermaking procedures that employ water as a solvent. In addition, it proposes specific methods to optimize the safety features of these paper-based cells and to improve the electronic conductivity of the electrodes by means of a carbonization process- an interesting novel technology that enables higher current rate capabilities to be achieved. The in-depth descriptions of materials, methods, and techniques are complemented by the inclusion of a general overview of electrochemical devices and, in particular, of different Li-ion battery configurations. Presenting the outcomes of this important research, the work is of wide interest to electrochemical engineers in both research institutions and industry.
Electrochemical power sources -- Lithium-based batteries -- Methods and materials -- Electrode preparation exploiting filtration -- Electrode preparation exploiting the spray coating technique -- Li-ion cell separator -- Carbonization procedure towards highly conductive paper electrodes.
Keywords: Materials; Nanotechnology; Energy storage; Electrochemistry; Materials Engineering; Nanotechnology; Mechanical and Thermal Energy Storage; Electrochemistry